1986
DOI: 10.1021/np50047a020
|View full text |Cite
|
Sign up to set email alerts
|

Preparative On-Line Overpressure Layer Chromatography (OPLC): a New Separation Technique for Natural Products

Abstract: overpressure layer chromatography (oplc) is further developed for the online preparative isolation of natural compounds. Its use is demonstrated for the rapid isolation of one or two compounds in less than 1 h as well as for the isolation of more substances from plant extracts andor prepurified fractions which require a few hours. Depending on the separation problem, sample sizes between 50 mg and 0.5 g may be applied to 20x20 cm silica plates. Principles of the method, practical considerations, and advantages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 3 publications
(3 reference statements)
0
9
0
Order By: Relevance
“…In order to optimize the mobile phase composition for a single development, the PRISMA method was then used (19,20 (7,9,11,(22)(23)(24)(25). OPLC has been shown to be a useful separation technique in natural products research for both analytical and preparative purposes (20,21,26,27). Using this technique, we are now able to separate cucurbitacins having an unsaturated side-chain from their corresponding 23,24-dihydro derivatives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to optimize the mobile phase composition for a single development, the PRISMA method was then used (19,20 (7,9,11,(22)(23)(24)(25). OPLC has been shown to be a useful separation technique in natural products research for both analytical and preparative purposes (20,21,26,27). Using this technique, we are now able to separate cucurbitacins having an unsaturated side-chain from their corresponding 23,24-dihydro derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…sample B could be separated into 3 and 4 in 20 mm. Based on these analytical results, a larger quantity (50mg each) of A and B was finally purified by using the OPLC on-line preparative method(21).Thefour isolates were then identified as 23,24-dihydrocucurbitacin-F-25-O-acetate (1), cucurbitacin-F-25-O-acetate (2), cucurbitacin-F (3), and 23,24-dihydrocucurbitacin-F (4), by comparison with authentic samples and/or by spectroscopic analysis ('H-and '3C-NMR, MS)…”
mentioning
confidence: 99%
“…The use of OPLC as an on-line preparative method is reported for the separation of cannabinoids (Oroszlan et al, 1987), poppy alkaloids, furocoumarins and secoiridoid glycosides (Nyiredy et al, 1986b), and for cytotoxic canthin-6-one alkaloids, epimeric cardiac glycosides (Erdelmeier et al, 1987), quassinoids and Podophyflum lignans (Erdelmeier et a f . , 1986).…”
Section: Planar Chromatograpfiymentioning
confidence: 99%
“…, 1986). This method has also proven useful for the rapid isolation or purification of single, major constituents from natural sources (Nyiredy et al, 1986b;Erdelmeier et al, 1987;Meksuriyen and Cordell, 1988;Fullas et a f . , 1989).…”
Section: Planar Chromatograpfiymentioning
confidence: 99%
“…However, early systematic studies were reported by Cornelis et al (95) and Bock et al (96). The structure of secogalioside (42), for example, was assigned by chemical correlation with sweroside (17) using 1H-and 13C-NMR data as well as NOB experiments, thus allowing the full structure determination including conformation as well as the absolute configuration (96). Furthermore, it has been shown that compounds like morroniside (43) exist as a mixture of C-7 anomers in solution leading to mutarotational equilibrium.…”
Section: Investigation Of Secoiridoid Glucosidesmentioning
confidence: 99%